Memotret Intagible Assets di Desa Tambakrejo dalam Mewujudkan SDG’S: Perspektif Human Capital - Mahanani, Qory Satiti; Mudrifah, Mudrifah; Irawan, Dwi (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2024)
This study aims to reveal how the role of the Tambakrejo Village government in implementing human capital in village development to support village SDGs. This research uses a descriptive qualitative approach in describing the implementation of human capital with data analysis techniques that refer to the Miles and Huberman model. Data were collected using documentation techniques and semi-structured interviews to measure the depth of information with informants. The informants of this research are Tambakrejo Village officials. The results of this study indicate that Tambakrejo Village has the ability to realize village development that can support village SDGs, especially in the indicators of quality village education (SDG's goal 4) and the involvement of village women (SDG's goal 5). Although not yet fully optimized, this ability is motivated by the motivation of the village government in transferring their skills and knowledge to provide the best service to support sustainable development for their community. The contribution of this research is to provide insight in mapping the potential to support the achievement of village SDGs. This study has limitations where researchers only focus on one component of IC, namely human capital. So that future researchers can add other IC components such as structural capital and relationship capital.